Simple IoT rain gauges are positioned to be a gamechanger in helping farmers manage agricultural risk - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Successful development process led to an engineering report, 80 prototypes dispatched to 6 countries. Field testing started during 2020 EA short rains. WebUI setup for real-time data visualization, analysis. ML workflow for semiautomated manual rain gauge data reading developed to support concurrent exploitation, interoperability between IoT and manually-operated networks .